PENGARUH LEMBAR KERJA SISWA BERBASIS INKUIRI TERBIMBING TERHADAP KETERAMPILAN PROSES SAINS - Erwan Feriyadi; Arwin Achmad; Rini Rita T. Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2015)
This study aimed to determine the effect of student work sheet guided inquiry based on improving Science Process Skill. Study design was pretest-posttest non-equivalent group. Samples were VII1 and VII2 that were chosen by Purposive Sampling. Quantitative data which were obtained from the average value of test were analyzed by t-test and U-test. The qualitative data were students Science Process Skill from the observation sheet and questionnaire responses that analyzed descriptively. The results showed that the N- gain average of exsperiment class was (70,78). Observation result of Science Process Skill has high criteria (80,54%), and most (85,48%) of the students gave positive respond to Student Work Sheet based on Guided Inquiry. Thus, the use of guided inquiry based worsheets could improved science process skill students in the subject matter of contamination and its impact on living.Penelitian ini bertujuan mengetahui pengaruh penggunaan Lembar Kerja Siswa berbasis Inkuiri Terbimbing dalam meningkatkan Keterampilan Proses Sains. Desain penelitian pretes-postes kelompok tak ekuivalen. Sampel penelitian siswa kelas VII1 dan VII2 SMP Negeri 1 Pagelaran dipilih secara Purposive Sampling. Data KPS siswa yang diperoleh dari nilai pretest, postest, dan N-gain yang dianalisis menggunakan uji-t dan uji-U. Data kualitatif KPS dan tanggapan siswa dianalisis secara deskriptif. Hasil penelitian Sd N-gain sebesar (70,78 18,97). Observasi KPS memiliki kriteria tinggi (80,54%) dan sebagian besar (85,48%) siswa memberikan tanggapan positif terhadap penggunaan LKS Inkuiri Terbimbing. Dengan demikian, penggunaan LKS berbasis Inkuiri Terbimbing dapat meningkatkan KPS siswa pada materi pokok pencemaran dan dampaknya bagi makhluk hidup.Kata kunci: keterampilan proses sains (KPS), LKS inkuiri terbimbing, pencemaran, dan dampaknya bagi makhluk hidup